2012
DOI: 10.1111/j.1600-0501.2012.02486.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Straumann Bone Level Implant system for anterior single‐tooth replacements in augmented and nonaugmented sites: A prospective cohort study with 60 consecutive patients

Abstract: From the present prospective, clinical study, it can be concluded that the Straumann Bone Level Implant shows an excellent survival rate, marginal bone stability and good clinical and aesthetic results. Bone augmentation before implant placement does not lead to more marginal bone loss. However, less favourable pink aesthetic outcomes were found in augmented sites compared with nonaugmented sites, while no differences were found between cement-retained and screw-retained restorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 29 publications
6
80
0
Order By: Relevance
“…The favorable radiographic changes observed in the current study are comparable to previously reported results. A mean bone loss of 0.10 ± 0.27 mm after a follow‐up of 18 months after Type 3 and 4 placements of Straumann ® bone level implants was reported in the anterior maxillary region . Type 2 placement of Straumann ® bone level implants has also been reported to exhibit minimal marginal bone changes (0.18 mm) after 3 years of loading .…”
Section: Discussionmentioning
confidence: 98%
“…The favorable radiographic changes observed in the current study are comparable to previously reported results. A mean bone loss of 0.10 ± 0.27 mm after a follow‐up of 18 months after Type 3 and 4 placements of Straumann ® bone level implants was reported in the anterior maxillary region . Type 2 placement of Straumann ® bone level implants has also been reported to exhibit minimal marginal bone changes (0.18 mm) after 3 years of loading .…”
Section: Discussionmentioning
confidence: 98%
“…Another reason for high PES in the present study could be that most of the implants were placed in non-grafted bone (16/19). This argument can be supported by studies that showed pink esthetic scores were significantly higher when implant placed in the non-grafted bone compared to implant treatment in conjunction with guided bone regeneration or implant placement in the grafted bone [11, 13, 22, 25]. …”
Section: Discussionmentioning
confidence: 98%
“…Tawse -Smith et al (2017) No implants presented bone loss >1 mm Cardaropoli et al (2006) 1 patient presented mucositis Santing et al (2013) 1 implant presented bone loss >2 mm Bae et al (2008) 0 cases of peri-implant infection Henriksson and Jemt (2003) It is mentioned that there were no signs of peri-implant infection and that bone loss was between 1 and 2 mm Nothdurft and Pospiech (2010) It is not specified the cases with peri-implantitis, but 7 implants lost more than 2 mm Vanlioglu et al (2012) No single case with bone loss >0.5 mm Hosseini et al (2013) 2 buccal fistulas in the zirconia group without bone loss. 1 implant in the gold group presented bone loss of 2.5 mm.…”
Section: Reference Main Findingsmentioning
confidence: 99%
“…The patient's aesthetic perception was evaluated by means of a visual analogue scale (VAS) in six studies (Baldini et al 2016;Carrillo de Albornoz et al, 2014;Fenner et al, 2016;Hosseini et al, 2011;Nilsson et al, 2017;Schepke et al, 2017) and by means of a questionnaire in four (Hosseini et al, 2013;Santing et al, 2013;Vanlioglu et al, 2012;Wannfors & Smedberg, 1999). The patient's aesthetic perception was evaluated by means of a visual analogue scale (VAS) in six studies (Baldini et al 2016;Carrillo de Albornoz et al, 2014;Fenner et al, 2016;Hosseini et al, 2011;Nilsson et al, 2017;Schepke et al, 2017) and by means of a questionnaire in four (Hosseini et al, 2013;Santing et al, 2013;Vanlioglu et al, 2012;Wannfors & Smedberg, 1999).…”
Section: Patient-reported Outcome Measures (Proms)mentioning
confidence: 99%